Survey Perilaku Hidup Bersih Dan Sehat (PHBS) Siswa SMP Negeri 1 Pakisjaya - Khoirullah; Setio Nugroho; Rolly Afrinaldi; Deden Akbar Izzuddin (Jurnal Literasi Olahraga, 2021)
The problem that becomes the reference in this research is How big is the Clean and Healthy Life Behavior (PHBS) of students of SMPN 1 Pakisjaya? Based on the above problems, the purpose of this study is to determine the Clean and Healthy Life Behavior (PHBS) of students of SMPN 1 Pakisjaya. This study used a survey method with a descriptive quantitative approach. There is a sampling using random sampling technique, with a total sample of 83 students at Pakisjaya State Junior High School. The data collection tool to measure Clean and Healthy Behavior (PHBS) uses a Clean and Healthy Life Behavior Questionnaire (PHBS). From the results of this study, it is known that the Clean and Healthy Behavior of SMP Negeri 1 Pakisjaya students stated that they were in the "very good" category with a percentage of 50.6%, in the "good" category with a percentage of 19. 3%, in the "quite good" category with a percentage of 22.9%, in the "not good" category with a percentage of 0%, and in the "very poor" category with a percentage of 7.2%. So it can be concluded that the Clean and Healthy Behavior of SMP Negeri 1 Pakisjaya students is Very Good.